Educational Process as Something Dynamic - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2023)
If we conceive the educational process as something dynamic, which basically combines what is given with what is emerging, we will understand that there are protagonists in it who have a fundamental role in this process, or perhaps we should say that, in this process, each and every one of the agents has a leading role. So, talking about curriculum implies that the subject can be approached from different perspectives, some more legitimate than others, some broader than others and, what is even more notorious, some more dynamic than others. It is in these differences where the essence of the educational process is conjugated, namely, in the conception of the curriculum, so it is worth asking: What are the educational units understanding by "development of their own curricular projects"? What are they actually doing? What curricular decisions do they make? Not only these questions arise, but many more, not to mention that it is also legitimate to doubt the capacity and preparation of teachers and educational units to undertake a process of conscious and responsible construction of an effective curriculum. It is interesting to approach the subject critically, not to reconsider the theoretical aspects, in which we find a wide range of postulates, but rather to revitalize the pedagogical practice in the place where it actually occurs, the classroom, and from there to enable discussion. and analysis of the problem, assuming that a paradigm change is urgent at all levels, otherwise, the entire society will suffer even more marked dehumanization. There are many challenges and requirements that fall on the educational task, and there are many who express their opinion, judge and dare to formulate lapidary sentences on the subject of education, with no more foundation than that allowed by a fragmented look at reality, therefore Therefore, a deeper look can shed light on why it has not yet been possible to reach a more optimal level in the quality indices, nor has equity been achieved, and what is worse, it seems that all that has been said is slipping away. through the window of the classrooms to end up in the realm of abstraction, from which it will not be possible to bring what is real and everyday. Thus, this work will also be a proposal for educational agents, a proposal that should not be kept together with others, but rather, hand in hand with the contingent, could give way to a better understanding of the problem.